The Artificial-Liver Blood-Purification System Can Effectively Improve Hypercytokinemia for COVID-19 - Guo, Jing; Xia, He; Wang, Shuting; Yu, Liang; Zhang, Huafen; Chen, Jun; Shi, Ding; Chen, Yanfei; Zhang, Yan; Xu, Kaijin; Xu, Xiaowei; Sheng, Jifang; et al. (Frontiers in Immunology, 2020)
Since December 2019, the outbreak of Coronary Virus Disease 2019 (COVID-19) occurred in Wuhan, and rapidly spread across the country, and the world. As the number of diagnoses and deaths continues to rise, this has become the focus of international public health. COVID-19 is highly contagious, and there is no effective treatment. New treatment strategies are urgently needed to improve the treatment success rate of severe and critically ill patients. Increasing evidence has shown that cytokine storm plays an important role in the progression of COVID-19. The artificial liver blood purification system (ALS) is expected to improve the cytokine storm. In the present study, the levels of cytokines and chemokines were detected in 12 COVID-19 patients before and after ALS, and exciting results were obtained. The present study has directly proven that ALS can block the cytokine storm, rapidly remove the inflammatory mediators, and hopefully suppress the progression of the disease, providing a new idea for the clinical treatment of COVID-19.